DEMOCRATIC CONSOLIDATION OR LEGITIMACY CRISIS? THE DYNAMICS OF INDONESIA’S POLITICAL SYSTEM AFTER THE AUGUST 2025 RIOTS - I Gede Sujana; Stefanus Dede Ngara; Albertus Taek; Maria Anjelina Bulu; Yublina Kalli (International Journal of Education and Social Science Studies, 2025)
The August 2025 riots represent a critical juncture in Indonesia’s democratic trajectory, exposing deep structural tensions between institutional reform, social polarization, and the erosion of political legitimacy. This study investigates how Indonesia’s post-riot political dynamics reveal the coexistence of democratic consolidation and legitimacy crisis within a single political framework. Employing a descriptive qualitative design, the research analyzes thirty policy documents, major national media reports, and fifteen semi-structured interviews with political elites, scholars, and civil society activists conducted between August and December 2025. The findings demonstrate that while procedural reforms and public participation have expanded—particularly in local governance—persistent elite fragmentation, uneven policy implementation, and ineffective political communication have continued to weaken institutional credibility. These dynamics suggest that democratic consolidation in emerging regimes may not follow a linear path toward stability but instead generate new forms of legitimacy deficit. The study contributes to broader comparative debates by illustrating that consolidation and crisis are intertwined processes, challenging conventional models of democratic endurance in post-authoritarian contexts.